Persepsi Masyarakat Terhadap Calon Incumbent Study Pilkada Di Kabupaten Trenggalek - Khasanah, Roudhotul Uswatun; Yulianti, Cindy Khofifah; Nur Kumala, Mila; Purnawati, Laily (CV Kalimasada Group, 2024)
In the 2024 District Head Election in Trenggalek Regency, two contenders will face off against blank ballots. What makes this candidate unique for Trenggalek Regency is that they have both served as Regent and Deputy Regent. The purpose of this research is to learn how voters in the Trenggalek Regency felt about the current regional office holders. This study applies the principle of rational action as out by Max Weber. The results of the Trenggalek Regency Election are consistent with Max Weber's notion of rational choice. This research is descriptive in nature and employs a qualitative methodology. Research on public perception of incumbent candidates in the Trenggalek Regency regional elections found that, on average, Trenggalek residents favor candidates with well-defined platforms and strong support for local initiatives. Additionally, residents of Trenggalek believe that the current incumbent has done an excellent job leading the regency in all areas of development, and they believe that the current defense should be re-elected for another five years. This research concludes that the public views incumbent candidates differently depending on their reputation, experience, and abilities.